16. The Effect of Indigofera sp. Leaf on the Protein Level of Rabbit Meat (Orictolagus sp) - Yuza Al Iqwal; Rastina Rastina; Abdul Harris; T. Reza Ferasyi; Al Azhar; Muslim Akmal (Jurnal Medika Veterinaria, 2018)
This study aimed to determine the effect of Indigofera sp. leaf to increase protein content of rabbit meat (Origtolagus sp). This study used a complete randomized design, consisted of 3 treatments and 3 replications. The samples were nine local male rabbits aged two months. P0 was control group which was given commercial feed, P1 was given 80% commercial feed and 20% Indigofera sp. pellet leaf, and P2 was given 70% commercial feed and 30%  Indigofera sp. pellet leaf. The feeding and drinking was conducted at 07:00 to 08:00 am and at 04:00 to 05:00 pm ad libitum. Protein content was measured using Kjeldahl method after eight weeks of treatments. The data was analyzed using Analysis of Variance (ANOVA) with SPSS v16.0 for Windows. The results showed that mean value (±SD) of meat protein for P0, P1 and P2 were 18.79+0.81%, 19.40+0.33% and 20.88+0.74%, respectively. We can conclude that the leaves of Indigofera sp. was highly significant (P0,01) in increasing protein level of rabbit meat at a concentration of 30%.